STUDYING THE STRATEGIES OF BEHAVIOR IN PATIENTS WITH PULMONARY TUBERCULOSIS WITH MULTIPLE DOSING STABILITY AND LOW AGREEMENT TO TREATMENT - Djurabaeva, M.Kh.; Anvarova, E.V.; Rakhmanov, Sh.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To study the emotional, motivational, and cognitive components of the relationship to the disease in patients with pulmonary tuberculosis with multidrug resistance (MDR / TB of the lungs). Material and Methods: 32 patients with multidrug-resistant pulmonary tuberculosis who received a standard chemotherapy regimen with backup anti-TB drugs were supervised. The object of empirical research is 72 people (42 women and 30 men), who were divided into 3 groups: Group 1 (control) - 40 people without somatic diseases, Group 2 - 18 newly diagnosed patients with MDR / TB lungs, 3rd group - 14 re-treated patients with MDR / TB of the lungs. Results: as the observations showed, patients with drug-resistant pulmonary tuberculosis tend to exhibit non-positive emotional reactions, resorting to aggressive communication strategies, while after a step-by-step retesting program, an increase in compliance and long-term treatment was observed. Conclusions: according to the results of the study, a step-by-step program of work with patients with MDR / TB of the lungs who have difficulties in social adaptation has been developed.